2008
DOI: 10.1103/physrevb.77.165322
|View full text |Cite
|
Sign up to set email alerts
|

Competition between confinement potential fluctuations and band-gap renormalization effects inIn0.53Ga0.47As/In

Abstract: We present the results of our studies on the emission properties of In 0.53 Ga 0.47 As/ In 0.525 Ga 0.235 Al 0.25 As single and coupled double quantum wells ͑CDQWs͒ with different degrees of potential fluctuation. We have verified that the curve of the temperature ͑T͒ dependence of the emission peak energy ͑E PL ͒ is significantly influenced by the potential fluctuations ͑which are magnified by the presence of the internal barrier in the CDQW͒ as well as by the excitation density used in the photoluminescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…Below T X , the potential fluctuations dominate the excitonic transitions, and for temperature values superior than T X , the effect of band-gap energy renormalization starts to predominate. 18,19 Taking this into account, it can be observed that on ͑311͒ surfaces, the values of T X are higher than those on ͑100͒, showing that the potential fluctuations are higher in those surfaces.…”
Section: ͑4͒mentioning
confidence: 99%
See 1 more Smart Citation
“…Below T X , the potential fluctuations dominate the excitonic transitions, and for temperature values superior than T X , the effect of band-gap energy renormalization starts to predominate. 18,19 Taking this into account, it can be observed that on ͑311͒ surfaces, the values of T X are higher than those on ͑100͒, showing that the potential fluctuations are higher in those surfaces.…”
Section: ͑4͒mentioning
confidence: 99%
“…[17][18][19][20] As far as we know, studies about the influence of substrate orientation on potential fluctuations in QWs are lacking. This article aims to analyze the influence of the substrate orientation on the potential fluctuations of GaAs/ Al x Ga 1−x As MQWs grown on ͓100͔ ͓311͔A, and ͓311͔B oriented GaAs substrates.…”
Section: Introductionmentioning
confidence: 99%
“…This should be the band edge displacement to lower energies; however, the band filling is also occurring, displacing the PL peak to higher energies, relative to the band edge. In a previous work, about the BGR effect in InGaAs/InGaAlAs CDQWs [34], we have found that for the same laser intensity range, the PL peak energy displacement to lower energies is about half of the band edge displacement, due to the combination of BGR and band filling effects. In order to make a back-of the envelope calculation, the same proportionality was considered in the present case and we found a displacement of the PL peak of about 3.4 meV, in a very good agreement with the experimental results of $3 meV for the CDQW5 and $ 4 meV for the CDQW30.…”
Section: Tablementioning
confidence: 92%
“…This is due to the fact that, as the fluctuations are deeper, it is necessary a higher excitation power to fill up all the localized states and, therefore, above a certain excitation power, the effects of band-tail (related to the potential fluctuations) filling and BGR cancel each other out, and the value of the PL energy peak remains practically constant [34].…”
Section: Tablementioning
confidence: 98%
See 1 more Smart Citation